Optimization of the Anodization Processing for Aluminum Oxide Gate Dielectrics in ZnO Thin Film Transistors by Multivariate Analysis - Gomes, Tiago C. [UNESP]; Kumar, Dinesh; Fugikawa-Santos, Lucas [UNESP]; Alves, Neri [UNESP]; Kettle, Jeff (American Chemical Society (ACS), 2019)
The present study reports a two-level multivariate analysis to optimize the production of anodized aluminum oxide (Al 2 O 3 ) dielectric films for zinc oxide thin-film transistors (TFTs). Fourteen performance parameters were measured and analysis of variance (ANOVA) of the combined responses has been applied to identify how the Al 2 O 3 dielectric fabrication process influences the electrical properties of the TFTs. Using this approach, the levels for the manufacturing factors to achieve optimal overall device performance have been identified and ranked. The cross-checked analysis of the TFT performance parameters demonstrated that the appropriate control of the anodization process can have a higher impact on TFT performance than the use of traditional methods of surface treatment of the dielectric layer. Flexible electronics applications are expected to grow substantially over the next 10 years. Given the complexity and challenges of new flexible electronics components, this multivariate approach could be adopted more widely by the industry to improve the reliability and performance of such devices.
Keywords: aluminum oxide; anodization; ANOVA; design of experiments; Plackett-Burman design; thin-film transistors